ACCURACY OF PRENATAL DETECTION OF CONGENITAL HEART ANOMALIES USING ULTRASONOGRAPHY: A SYSTEMATIC REVIEW: Pharmaceutical Science-Medicine - MOUSSA D. MAIMSH, OMAR; M. ALGORASHI, EMAN (International Journal of Life Science and Pharma Research, 2019)
Ultrasound examinations in the second trimester for detection of congenital malformations are now part of pregnancy care in most developed countries. Major heart defects can be diagnosed before birth by sonographic assessment of the four-chamber view. This review is aimed to evaluate the evidence published on the accuracy of prenatal detection of congenital cardiac anomalies using ultrasonography. A web-based search was conducted in MEDLINE database and eligible studies were identified and then screened against inclusion criteria such as detection of congenital heart anomalies and reporting of ultrasonography accuracy. The full texts were retrieved for eligible studies and secondary in-depth screening were conducted for the study against inclusion criteria. Data were extracted from our studies regarding study’s characteristics, type of heart anomalies and level of accuracy. The data were synthesized and discussed with qualitative approach. The electronic search resulted in 145 eligible studies. After screening of titles and abstracts of these articles, irrelevant and duplicated studies were excluded and finally full-texts of 13 articles were retrieved. Overall sample size was ranged between 31 to 4172 with gestational age ranged between 11 weeks to 41 weeks. Overall accuracy of ultrasonography in the prenatal detection of heart anomalies was ranged between 81% to 98.4%. Ultrasonography has fair to high accuracy in prenatal detection of heart anomalies. The variation depends on factors such as technology, experience of the operator, and type of the anomaly. The findings of the included studies showed an acceptable accuracy of ultrasonography in detection of heart anomalies either in high or low risk groups